Moisture Dependent Physical Properties of Multiplier Onion (Allium cepa L. var. aggregatum) - K, Gomathy; Balakrishnan, M.; Thirupathi, V. (Journal of Agricultural Engineering, 2017)
The physical properties of multiplier onion (CO-4) were studied as a function of moisture content in the range of 80.87 % to 88.84 % (w.b.). The geometrical, physical and frictional properties, namely size, true density, bulk density and coefficient of friction increased with increase in moisture content. The average equatorial diameter, polar diameter and thickness of onion ranged from 30.8 to 34.0 mm, 24.2 to 25.9 mm, 18.6 to 21.0 mm, respectively at a moisture range of 80.87 % to 88.84 % (w.b.). The true density ranged from 887.0 to 933.0 kg.m-3, whereas the bulk density of onion bulbs varied from 397.54 to 462.63 kg.m-3 at the above moisture range. The highest friction was offered by rubber, followed by cardboard, mild steel, galvanised iron and stainless steel. The porosity of onion decreased from 55.13 % to 50.39 % with increase in moisture content. Linear equations comprising the thickness, polar and equatorial diameter predicted the mass of onion bulbs with highest R2 value of 0.998.